Indigenous Maasai Perspectives on Availability of natural resources and Access to community livelihood resources in Masai Mara Wildlife dispersal area, Narok County, Kenya - Jane, Nyandika; Kioko, Musingi John; James M., Moronge (African Journal of Education,Science and Technology (AJEST), 2024)
Land tenure policy reform have reorganized Maasai living a natural resource scarce space in a wildlife dispersal area in Kenya. However, from the perspectives of Maasai Indigenous Peoples (IP) households who live in place, land productivity specifically; availability and access to environmental resources and community livelihood benefits dwindle in sedentary settlements within Mara ward, Narok south sub- County. A sample size of 183 households’ responses regarding benefits from goods and services during a land tenure change regime recorded dissatisfaction events by Maasai IP household heads. From the Mara ward case study findings; dissatisfaction of agro-pastoralist resource group to water resources (72.5%), forest (80.3%) and, dry season grazing land (80.7%) were high. Maasai respondents engaged in business activities were dissatisfied with access to mainly a dry season grazing land (52.9%). Mara households dissatisfied with all community benefits still: agro-pastoralists, expressed dissatisfaction with access to transport infrastructure (82.9%), schools (79.7%), shopping centre (78.9%) and livestock trade (76.3%). These findings depict a competition between livestock and business livelihood source models in Mara ward. Other underlying effects that were raised were, fences that make women and herders to walk longer distances to water and pasture respectively. The poorer Maasai IP households registered off-farm and casual labour engagement; an outcome that depict loss of pastoralism skills. By changing to sedentary lifestyle, 26 percent of younger Maasai household heads from Mara study sites chose to exit the agro-pastoral lifestyle to join hired labour force in nearby towns. In conclusion; land reform policy values and relational power enforce private property rights but, also incentivize to overexploit available natural resources needed by pastoral workforce in Mara, ward. As a recommendation; land reform institutions should prioritize a resilient wildlife dispersal area in order to improve poorer households’ access to livelihood sources for better land productivity and outcomes.